Influence of Contract Management Practices of Effective Communication, Trust Building and Conflict Resolution on Contract Completion in the Public Sector - Emmanuel Andrew Odere (Uganda Christian University, 2025)
The study sought to examine the influence of contract relationship management practices of effective communication, building trust and conflict resolution in the public sector, a case study on Jinja City Council (JCC). The study was guided by three objectives; examining the influence of effective communication on contract completion, examining the influence of trust building on contract completion in the public sector and examining the influence of conflict resolution on contract completion in the public sector.
Undergraduate